The inter-relationships among mobility, housing prices and innovation: evidence from China’s cities - Zhang, Juanfeng; Zhou, Jiangxing; Qian, Liyang; Zhang, Danxia; Han, Rui; Takawadiyi, Monalissa Tinotenda; Li, Lele (International Journal of Strategic Property Management, 2023)
The existing literature contends that high housing prices are a negative factor inhibiting population mobility and urban innovation. This paper explores the interaction effect among population mobility, housing prices and urban innovation. Based on panel data from the Yangtze River Delta region from 2010 to 2019, we establish a simultaneous equation model (SEMs) to test the relationship between population mobility, housing prices, and urban innovation vitality. The empirical results show that (1) population mobility and housing prices are positively correlated; (2) urban innovation vitality has a significant and positive effect on housing prices; (3) population mobility and urban innovation vitality are also positively correlated.